KAJIAN BENTUK RUANG DAN WARNA PADA BANGUNAN PENDIDIKAN PENYANDANG DISABILITAS - Sadeafani, Rheny; Melanira, Astria (Jurnal Ilmiah Arjouna: Architecture and Environment Journal of Krisnadwipayana, 2021)
This research focuses at the shape space and colors on a educational building for the disabled. This researchexplains about space for educational purposes, the layout of the building and the suitable and interesting facility,along with how colours affects the learning and teaching process of kids with special needs. This research aims tocreate space that can support the quality, character, effectiveness and efficiency towards the building users whichwould consist of mostly the disabled, and how choosing the correct color scheme could make a more positive andinspiring environment.